The Simulation of Museum Interior Experiences Through 3D Visualisation: The Comparison Study on Visitor Perception - Astrid Kusumowidagdo; Yusuf Ariyanto; Christina Jeanette (Wacana Seni Journal of Arts Discourse, 2025)
Enhancing the appreciation of museums among the younger generation is crucial for preserving cultural heritage, fostering education, and inspiring creativity. The interior experience at the Majapahit Information Centre Museum in Trowulan, Indonesia, plays a vital role in creating a welcoming and engaging atmosphere. This study aims to analyse the relationship between young visitors’ perceptions and their experiences in museum interiors, with a focus on comparisons between contemporary and traditional environments that emphasise local values. By attracting and involving younger visitors, museums can convey knowledge and promote cultural heritage, thereby supporting efforts to preserve cultural heritage. The study utilised a quantitative approach through an experimental survey involving 75 respondents who evaluated 3D visualisations of two simulated museum settings: one contemporary and one traditional. Descriptive statistics were used to analyse factors contributing to satisfaction with the space, including orientation and navigation, spaciousness and display density, design and display style, lighting, and colour. Findings indicate that museum interiors with contemporary styles significantly influence cognitive responses, particularly in terms of design style and appearance. Conversely, traditional interior styles significantly impact cognitive responses related to lighting factors, as well as the spaciousness and density of display. These insights offer valuable implications for designing museum environments that resonate with younger audiences and can guide future research in this area.